(3t+5s)(5t-s)=

Simple and best practice solution for (3t+5s)(5t-s)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3t+5s)(5t-s)= equation:


Simplifying
(3t + 5s)(5t + -1s) = 0

Reorder the terms:
(5s + 3t)(5t + -1s) = 0

Reorder the terms:
(5s + 3t)(-1s + 5t) = 0

Multiply (5s + 3t) * (-1s + 5t)
(5s * (-1s + 5t) + 3t * (-1s + 5t)) = 0
((-1s * 5s + 5t * 5s) + 3t * (-1s + 5t)) = 0

Reorder the terms:
((25st + -5s2) + 3t * (-1s + 5t)) = 0
((25st + -5s2) + 3t * (-1s + 5t)) = 0
(25st + -5s2 + (-1s * 3t + 5t * 3t)) = 0
(25st + -5s2 + (-3st + 15t2)) = 0

Reorder the terms:
(25st + -3st + -5s2 + 15t2) = 0

Combine like terms: 25st + -3st = 22st
(22st + -5s2 + 15t2) = 0

Solving
22st + -5s2 + 15t2 = 0

Solving for variable 's'.

Factor a trinomial.
(-5s + -3t)(s + -5t) = 0

Subproblem 1

Set the factor '(-5s + -3t)' equal to zero and attempt to solve: Simplifying -5s + -3t = 0 Solving -5s + -3t = 0 Move all terms containing s to the left, all other terms to the right. Add '3t' to each side of the equation. -5s + -3t + 3t = 0 + 3t Combine like terms: -3t + 3t = 0 -5s + 0 = 0 + 3t -5s = 0 + 3t Remove the zero: -5s = 3t Divide each side by '-5'. s = -0.6t Simplifying s = -0.6t

Subproblem 2

Set the factor '(s + -5t)' equal to zero and attempt to solve: Simplifying s + -5t = 0 Solving s + -5t = 0 Move all terms containing s to the left, all other terms to the right. Add '5t' to each side of the equation. s + -5t + 5t = 0 + 5t Combine like terms: -5t + 5t = 0 s + 0 = 0 + 5t s = 0 + 5t Remove the zero: s = 5t Simplifying s = 5t

Solution

s = {-0.6t, 5t}

See similar equations:

| (48x)/(x^2-1)=0 | | Y=-11x-1 | | q=40+8a+2a^2 | | 12t=8t-11t | | 7x^2+24-16=0x | | 8x-9=-3 | | 4c+7(9+3c)= | | -5=-18V | | 150+.40x=70+.80x | | ln(30-2x)=ln(x^2-x) | | ln(x-10)=10 | | h(x)=2x^2-8x+4 | | (W+4)w=24 | | 4(h-2)=-9(6+h) | | 16w+9-15w=w+9 | | 5(x-2)=3x-4solvex | | 4/7=14/x | | (12y^2e^2x-y)dx=dy | | 0=-16t^2+64t+192 | | d^2+-5d=0 | | 4/9*n=29 | | 17x^2+x=15 | | 12-3x=-5x-44 | | 2z=0.35-5z | | 3w+9=29-2w | | (1-y)(5y-7)=0 | | 11y/4 | | 3w+9=29-2 | | cos^2(x)-sin^2(x)+sin(x)=0 | | -6n-28=4n | | 21m+14n=-7 | | (x^4/y^5)^0.25 |

Equations solver categories